Fixed Gonadotropin-Releasing Hormone Antagonist Protocol Versus Flexible Progestin-Primed Ovarian Stimulation Protocol in Patients With Asynchronous Follicular Development During Controlled Ovulation Stimulation: A Retrospective Study - Dong, Mei; Sun, Li; Huang, Li; Wang, Fang; Zhang, Xiqian; Liu, Fenghua (Frontiers in Endocrinology, 2021)
Protocols utilizing gonadotropin-releasing hormone (GnRH) antagonists have emerged as mainstream procedures for ovarian stimulation; however, GnRH increases the risk for periodic cancellation of embryos. Therefore, this study aimed to compare the pregnancy outcomes of a fixed GnRH antagonist protocol and a flexible progestin-primed ovarian stimulation (fPPOS) protocol in patients with asynchronous follicular development during controlled ovulation stimulation and to explore the feasibility of converting patients undergoing a fixed GnRH antagonist protocol to an fPPOS protocol. This was the first retrospective study exploring the fPPOS protocol in patients with asynchronous follicular development, and it was conducted in a public reproductive medicine center from January to December 2020. We included infertile women. All participants were scheduled to undergo administration of a GnRH antagonist on the fifth day of controlled ovulation stimulation. The study group included 129 women who were converted from the fixed GnRH antagonist protocol to the fPPOS protocol for their asynchronous follicular development, while the antagonist group consisted of 258 women (ratio 1:2) who proceeded with a fixed GnRH antagonist protocol. On the second or third day of the menstrual period, 100–300 IU/day gonadotropin injections were administered. For patients who were converted to the fPPOS protocol, medroxyprogesterone acetate tablets at 10 mg/day were started on the fifth day of stimulation or when only one leading follicle reached 14 mm and the other follicles were ≤10 mm in diameter, whichever came first. The rates of embryo implantation, clinical pregnancy, and early pregnancy loss were obtained. The number of oocytes retrieved and the number of high-quality embryos in the antagonist group were significantly higher than those in the fPPOS group (P = 0.039 and P = 0.025, respectively). No significant differences in the rates of embryo implantation, clinical pregnancy, and early pregnancy loss were observed between the two groups. Our study found that in patients who were scheduled for administration of GnRH antagonists but presented with asynchronous follicular development on the fifth stimulation day, it was feasible to switch to the fPPOS protocol.